Thermal kinetics of PFAS and precursors in soil: Experiment and surface simulation in temperature-time plane. (March 2023) - Al Amin, Md; Luo, Yunlong; Nolan, Annette; Mallavarapu, Megharaj; Naidu, Ravi; Fang, Cheng
Abstract: Per- and polyfluoroalkyl substances (PFAS) are chemically and thermally stable due to the presence of carbon-fluorine (C–F) bond in their molecular structures, hence have been previously formulated as firefighting ingredients. During the firefighting process, however, owing to the high temperature, PFAS can be potentially degraded, particularly for PFAS precursors that contain non-C-F bonds, which is studied herein by exposing PFAS-contaminated soil in a muffle furnace oven. Different temperatures and time intervals are applied to the real soil sample to mimic the firing process and to evaluate the degradation and conversion of PFAS. This thermal treatment can not only degrade precursors (e.g. 6:2 fluorotelomer sulphonate), but also degrade perfluoroalkyl carboxylates (PFCA, e.g. perfluorooctanoic acid PFOA) and perfluoroalkyl sulfonates (PFSA, e.g. perfluorooctane sulfonate PFOS). The concentration dependence of the PFAS on temperature and time is fitted using a 2D Gaussian surface to simulate the complex thermal kinetic, and to compare with the traditional approach such as thermogravimetric analysis (TGA) (1D dependence on temperature only). The 2D simulation can directly visualise the thermal kinetic of individual or sum PFAS in the complex temperature-time plane, which depends on the sample background and particularly on the coexist PFAS precursors. Overall, this study provides a simple approach to monitor and optimise the thermal treatment of the PFAS-contaminated soil. Graphical abstract: Image 1 Highlights: PFAS in soil have different and complicated thermal kinetics. 2D simulation can visualise the thermal kinetics from the time-temperature plane. Gaussian surface can predicate and optimise the thermal treatment via centroid. Competition between release from precursor and oxidation to end product is validated. Sample preparation such as soil drying might be problematic, because it can amend the initial concentration of PFAS.